Developing Vietnam's human resources in the context of the current Industrial Revolution and international integration - Le Thi Huong; Vu Thi Thu Trang; Le Hong Quang (Heritage and Sustainable Development)
Human resources are the foundation of a nation's success and development, reflecting social progress, equity, and sustainable growth. Vietnam has prioritized improving human resource quality as a strategic breakthrough to transform its socio-economic development model and enhance competitiveness in a globalized world. The Communist Party of Vietnam has issued policies emphasizing the integration of education and training with scientific research, technological innovation, and practical applications in production and business. Bold educational reforms aim to maximize human potential, leveraging opportunities from the Industrial Revolution 4.0 to accelerate industrialization and modernization. Key elements of human resource development in Vietnam include physical health, intellectual capacity, ethics, responsibility, professional skills, and workplace discipline. The focus is not only on technical expertise but also on fostering creativity, adaptability, and responsibility to meet the challenges of a rapidly changing world. Aligning human resource development with national goals, Vietnam aims to build a prosperous, equitable, and happy society. This article explores Vietnam’s strategies for human resource development in the context of the Industrial Revolution 4.0, highlighting its role in driving sustainable growth and global integration. A mixed-methods research approach, combining qualitative interviews with policymakers and quantitative surveys, is used to evaluate the effectiveness of these strategies. This research provides a comprehensive assessment of Vietnam’s human resource development initiatives, examining their alignment with national goals and their impact on socio-economic development. The findings aim to ensure that human resource development strategies are effectively implemented to foster sustainable growth and enhance Vietnam's global competitiveness.